Hong Kong Drug Allergy Delabelling Initiative (HK-DADI) consensus statements for penicillin allergy testing by nonallergists - Li, Philip H.; Wong, Jane C. Y.; Chan, Jacky M. C.; Chik, Thomas S. H.; Chu, M. Y.; Ho, Grace C. H.; Leung, W. S.; Li, Timothy C. M.; Ng, Y. Y.; Shum, Rocky; Sin, Winnie W. Y.; Tso, Eugene Y. K.; et al. (Frontiers in Allergy, 2022)
Introduction Penicillin allergy testing has been traditionally performed by allergists but there remains a huge deficit of specialists. A multi-disciplinary effort with non-allergists would be invaluable to overcome the magnitude of penicillin allergy labels via the Hong Kong Drug Allergy Delabelling Initiative (HK-DADI). These consensus statement (CS) offer recommendations and guidance to enable non-allergists to screen for low risk (LR) patients and perform penicillin allergy testing. Methods CS were formulated by the HK-DADI Group by the Delphi method. Agreement was defined as greater than or equal to 80% consensus. Results A total of 26 CS all reached consensus after multiple rounds of Delphi. CS were categorized into risk assessment, skin testing, drug provocation testing (DPT) and post-testing management. For risk assessment, the essentials of an allergy history and exclusion criteria were detailed. Patients with only LR features can proceed with testing by non-allergists. Skin tests should be performed prior to DPT. Details regarding the timing, preparation and interpretation of skin tests were detailed. DPT remains the gold standard to diagnose genuine allergy or tolerance and should be performed when there is a low pre-test probability following negative skin testing. Details of DPT preparations, dosing protocols and interpretation were detailed. For post-testing management, inaccurate allergy labels should be delabelled following negative DPT with proper patient counselling. Conclusion CS support penicillin allergy testing by non-allergists in Hong Kong. LR cases can be managed by non-allergists at Spoke Clinics, with training and support of an allergist-led Hub.